Plasmon-Enhanced Photoluminescence of an Amorphous Silicon Quantum Dot Light-Emitting Device by Localized Surface Plasmon Polaritons in Ag/SiOx:a-Si QDs/Ag Sandwich Nanostructures - Tsung-Han Tsai; Ming-Yi Lin; Wing-Kit Choi; Hoang Yan Lin (International Journal of Photoenergy, 2015)
We investigated experimentally the plasmon-enhanced photoluminescence of the amorphous silicon quantum dots (a-Si QDs) light-emitting devices (LEDs) with the Ag/SiOx:a-Si QDs/Ag sandwich nanostructures, through the coupling between the a-Si QDs and localized surface plasmons polaritons (LSPPs) mode, by tuning a one-dimensional (1D) Ag grating on the top. The coupling of surface plasmons at the top and bottom Ag/SiOx:a-Si QDs interfaces resulted in the localized surface plasmon polaritons (LSPPs) confined underneath the Ag lines, which exhibit the Fabry-Pérot resonance. From the Raman spectrum, it proves the existence of a-Si QDs embedded in Si-rich SiOx film (SiOx:a-Si QDs) at a low annealing temperature (300°C) to prevent the possible diffusion of Ag atoms from Ag film. The photoluminescence (PL) spectra of a-Si QDs can be precisely tuned by a 1D Ag grating with different pitches and Ag line widths were investigated. An optimized Ag grating structure, with 500 nm pitch and 125 nm Ag line width, was found to achieve up to 4.8-fold PL enhancement at 526 nm and 2.46-fold PL integrated intensity compared to the a-Si QDs LEDs without Ag grating structure, due to the strong a-Si QDs-LSPPs coupling.